Legal Regimes for State Property Management. / Regímenes legales para la gestión estatal de la propiedad - Krasyukova, Natalia L.; Rozhdestvenskaya, Irina A.; Eremin, Sergey G.; Galkin, Andrey I.; Alyautdinov, Nail F. (Utopía y Praxis Latinoamericana)
ABSTRACT Article deals with administrative-legal mechanism of state property management on example of the Russian Federation and the Republic of Belarus. Modern science is interested in comparative analysis of approaches to the management of state property in the States under consideration. The criteria of inclusion of objects in the state property formulated based on the existing legal relations allow the author to conclude that the subject of state property management is interested in the possibility of exercising the right of management, which will be the basis for determining such property as the object of such management. RESUMEN El artículo trata sobre el mecanismo administrativo-legal de la administración de bienes estatales, por ejemplo, la Federación de Rusia y la República de Belarús. La ciencia moderna está interesada en el análisis comparativo de los enfoques para la administración de la propiedad estatal. Los criterios de inclusión de objetos en la propiedad estatal formulados en base a las relaciones legales existentes permiten a los autores concluir que el sujeto de la administración de la propiedad estatal está interesado en la posibilidad de ejercer el derecho de administración, que será la base para determinar dicha propiedad como objeto de dicha gestión.